Effect of clove extract pretreatment and drying conditions on lipid oxidation and sensory discrimination of dried omena (Rastrineobola argentea) fish. (23rd July 2016) - Slavin, Margaret; Dong, Mengyi; Gewa, Constance
Summary: Sun‐drying is a low‐cost, low‐technology fish preservation method frequently employed in developing areas. However, the process promotes lipid oxidation and its associated undesired flavours and odours. This study investigated low‐technology solutions for impact on lipid oxidation and sensory attributes of oven‐dried omena fish ( Rastrineobola argentea ). Two oven‐drying conditions and four doses of clove water extract 'dip' pretreatments were studied in a complete factorial design. Lipid oxidation in dried fish was assessed by TBARS, peroxide value and fatty acid analysis by GC‐FID. Results showed that soaking in 10 g L −1 clove water extract for 1 h and oven‐drying at 150 °C × 30 min significantly reduced TBARS and peroxide values in omena fish by 77% and 79%, respectively, and polyene index showed improved retention of long‐chain polyunsaturated fats, compared to original drying condition. Lastly, panellists of a triangle test were able to discriminate between biscuits made with the modified and original dried fish. Abstract : Experimental flowchart. Chemical assays of lipid oxidation were used to measure the effectiveness of oven‐drying conditions and clove water extract pre‐treatment of omena fish for the ability to minimize lipid oxidation. Following identification of the treatment producing the least oxidation, a sensory evaluation was performed to determine if a fish biscuit product containing the modified dried fish could be discriminated from fish prepared by the original method.